KORELASI ANTARA KEMAMPUAN BERPIKIR KRITIS DAN SIKAP SAINS SISWA DENGAN HASIL BELAJAR BIOLOGI KELAS XI MAN 2 PEKANBARU - Ayu, Ayu; Darmawati, Darmawati; Suryawati, Evi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study was aimed to find out the correlation between critical thinking skills and science attitudes of students with biology learning outcomes of class XI MAN 2 Pekanbaru. This research was conducted at MAN 2 Pekanbaru which has been collected from May to October 2019. Samples were taken by purposive sampling technique. The sample used in this studywerestudents of class XI MIA 2 (28 students) and class XI MIA 8 (27 students). The variables that have been observedwere critical thinking abilities and science attitudes and questions and questionnaires on critical thinking skills and science attitude questionnaires were used as the instruments test. Furthermore, the data were analyzed by product moment correlation analysis at 5% level with student learning outcomes. The critical thinking ability of class XI MIA 2 has a correlation of 0.442 with learning outcomes while class XI MIA 8 has a correlation of 0.459 with learning outcomes. The attitude of science class XI MIA 2 has a correlation of 0.703 with learning outcomes while class XI MIA 8 has a correlation of 0.543 with learning outcomes. Based on the results of this study it can be concluded that class XI MIA 2 and class XI MIA 8 have a strong correlation between the ability to think critically and the attitude of science with biology learning outcomes namely class XI MIA 2 by 0.720 and class XI MIA 8 by o, 6.Key Words: Correlation, Critical Thinking Skills, Science Attitude, Learning Outcomes